EXPLORING THE CORRELATION BETWEEN DEPRESSION AND QUALITY OF LIFE IN OLDER ADULTS - Agarwal, Paridhi; Saxena, Rashmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Depression is a prevalent and incapacitating condition that diminishes quality of life (QOL) and increases the risk of mortality in older individuals (60 years of age and older). The relationship between depression or depressive symptoms and quality of life (QOL) has been the subject of increased attention in recent research. However, there is a scarcity of reviews that can assist us in understanding this relationship in older individuals. Given this, we conducted a literature review to ascertain the relationship between depression and quality of life in older individuals. The organ systems’ capacity to maintain homeostasis and reserve capacity, adapt to their surroundings, and mount a stress response is diminished as a result of the inevitable aging of every living object. Low energy, chronic anguish, discouragement, and a lack of interest in activities and self-worth are characteristic of depression, a common mental problem and medical illness. The concept of quality of life encompasses an individual’s perception of their level of contentment and enjoyment in life, as well as their perception of their role in relation to the culture and value systems in which they reside, and their expectations, beliefs, and concerns regarding their physical health. Materials and methodology- For this study, 45 participants were approached. The study was conducted using MMSE in older adults living in residential areas of Lucknow and 45 responses were collected. Spearman’s correlation test was performed to find correlation between Depression and Quality of Life. RESULT- Result showed that there is positive correlation between GDS and SF-12 Mental while there is negative correlation between GDS and SF-12 Physical. CONCLUSION- There is moderate to high correlation between depression and quality of life in geriatric population.